METTL3 Promotes Activation and Inflammation of FLSs Through the NF-κB Signaling Pathway in Rheumatoid Arthritis - Shi, Wen; Zheng, Yan; Luo, Shuai; Li, Xiaofeng; Zhang, Yilong; Meng, Xiaoming; Huang, Cheng; Li, Jun (Frontiers in Medicine, 2021)
Rheumatoid arthritis, a common autoimmune disease accompanied by high incidence, which is extremely harmful to human health. Fibroblast-like synovial cells have a vital role in the occurrence and development of RA. METTL3 is involved in the progression of many diseases, which is crucial component of the m6A methyltransferase complex. In this study, we discussed the role of METTL3 in proinflammatory and proliferation, invasion and migration of FLSs. We used the AIA model as an animal model of RA. Experimental results revealed that METTL3 expression is up-regulated obviously in RA synovium and AIA models. Silencing METTL3 suppressed TNF-α, IL-1β, IL-6, MMP3 and MMP9 levels in RA and AIA FLSs. On the contrary, they were increased by overexpression of METTL3. At the same time, we found that in FLSs, METTL3 may activate NF-κB signaling pathway. The experimental results showed that METTL3 may promote FLSs activation and inflammatory through the NF-κB signaling pathway.